Constantin Ardeleanu, „O croazieră de la Viena la Constantinopol. Călători, spaţii, imagini: 1830-1860”. Bucureşti, Ed. Humanitas, 2021, 302 p. - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2023)
In a bibliography of the Romanian cultural history of 19th century, Constantin Ardeleanu’s book must absolutely be included. It represents a necessary contribution to a field hitherto less considered in Romanian historiography, one that is at the meeting point between political history – historical geography – history of travel – history of transport, and not least, the history of literature and visual sources.